FAKTOR-FAKTOR YANG MEMPENGARUHI WAKTU TANGGAP (RESPONSE TIME) PERAWAT TERHADAP TINGKAT KEPUASAN PELANGGAN DI AGD DINKES DKI JAKARTA WILAYAH BARAT - Siti Nur Khasanah; Yeni Koto; Arif Hidayatullah (JOURNAL SAINS STUDENT RESEARCH, 2024)
Response time is a speed in a service or action quickly and accurately to patients. Response time has several factors that can affect and help the nurse's response time when carrying out an evacuation, including emergency training, length of service, education, patient condition, infrastructure and facilities, completeness of drugs and equipment, presence of officers, SISRUTE (Integrated Referral System), and workload. The purpose of this study was to determine the factors that affect the nurse's response time to the level of customer satisfaction at the AGD Dinkes DKI Jakarta Barat Region in 2023. The research method that will be used is an analytical research design with a correlational design cross-sectional approach and using the non-parametric Rank Spearman Ro test, a population of 80 respondents, a total sample technique and a sample size of 80 respondents. The results showed a relationship between emergency training and customer satisfaction (p-value 0.034); there was no relationship between length of service and customer satisfaction (p-value 0.559); there was no relationship between education and customer satisfaction (p-value 0.234); there is a relationship between patient conditions and customer satisfaction (p-value 0.005); there is a